Crystal Structure and Properties of 7‐Imino‐3‐Nitroimino‐2, 4, 6, 8‐Tetraazabicyclo[3.3.0]Octane Hydrochloride1. Issue 9 (2nd May 2016) - Jin, Xinghui; Hu, Bingcheng
Abstract: The chemical and physical properties of the energetic intermediate 7‐imino‐3‐nitroimino‐2, 4, 6, 8‐tetraazabicyclo[3.3.0]octane hydrochloride (compound A) were investigated. The crystal structure and thermal behavior were measured by X‐ray diffraction and TG‐DTG‐DSC coupling system, respectively. The electronic structure was also studied by electronic density, nature bond orbital charges, frontier molecular orbital, density of state, and electrostatic potentials. Compound A crystallizes orthorhombic in space group Pna 21 . Thermodynamic properties indicate that it has moderate thermal stability with a sharp exothermic peak (298.5 °C, 10 K· min –1 ) and high critical temperature of thermal explosion (558.5 K). The positive electrostatic potentials of compound A were stronger than that of the negative electrostatic potentials, which can stabilize the molecule. Compound A can also be considered as an energetic intermediate, which may shine light on the exploring of other 7‐imino‐3‐nitroimino‐2, 4, 6, 8‐tetraazabicyclo[3.3.0]octane hydrochloride based high density energetic materials. Abstract :